Perlindungan Hukum Perbankan Terhadap Konsumen dalam Layanan Electronic Payment Melalui Penggunaan QRIS dalam Mendukung Ekonomi Digital - Salma, Lina; Sinta Agustin, Mutiara; Sari, Chintia (UNIVERSITAS SERAMBI MEKKAH, 2025)
QRIS (Quick Response Code Indonesian Standard) is a standardization policy from Bank Indonesia to set electronic payment standards in Indonesia, which aims to ensure security, convenience, and uniformity in digital transactions. QRIS uses the Merchant Presented Mode (MPM) system, where users simply scan the QRIS code at the merchant without the need to change the digital payment application they use, which makes transactions faster, easier, and safer, and provides practical solutions, especially for small businesses that can receive payments from all payment system service provider (PJSP) applications with one account. This research uses a normative juridical method by analyzing the laws and regulations governing QRIS, as well as its relevance to the protection of consumer rights. The results show, although QRIS provides various advantages in terms of ease of transactions and protecting consumers (in data security), its application is still not effective. One of the reasons is the low literacy about digital finance and the lack of public understanding of this policy. Thus, intensive efforts are needed in socialization and education, as well as stricter supervision of the implementation of security standards in transactions through QRIS.